Effect of fampridine on axonal excitability in multiple sclerosis. Issue 7 (July 2016) - Huynh, William; Pickering, Hannah; Howells, James; Murray, Jenna; Cormack, Christine; Lin, Cindy S.-Y.; Vucic, Steve; Kiernan, Matthew C.; Krishnan, Arun V.
Highlights: Fampridine, a sustained-release form of 4-aminopyridine has been demonstrated in clinical trials to be effective in improving disability and fatigue in multiple sclerosis. An in vivo study of fampridine effects on axonal function. Fampridine administered at recommended therapeutic doses, has clear effects on nerve excitability in MS patients which are likely governed by modulation of fast K + channels. Abstract: Objective: To investigate the effects of fampridine on nerve excitability, the present study utilized peripheral axonal excitability techniques in 18 MS patients receiving treatment with fampridine. Methods: Studies were performed at baseline and repeated 3 months after institution of fampridine at standard dosing. Results: Following treatment with fampridine there were significant changes in axonal excitability for those parameters associated with fast K + channels that shifted towards normal control values. Specifically, increases were noted in the peak superexcitability of recovery cycle (fampridine, −25.6 ± 1.6%; baseline −22.8 ± 1.7%; p < 0.004), peak depolarizing threshold electrotonus (fampridine, 69.1 ± 1.0%; baseline 67.0 ± 1.4%; p < 0.004), and depolarizing threshold electrotonus between 40 and 60 ms after onset of depolarization (fampridine, 52.8 ± 1.3%; baseline 49.9 ± 1.4%; p = 0.02). Conclusion: The present study has established that fampridine at standard doses exerts effects on peripheral nerve function that may be mediated by reduction of fast K + conductances. Significance: Modulation of fast K + conductances by fampridine may contribute to the improvement observed in MS symptoms including motor fatigue.